2017
DOI: 10.1155/2017/6824385
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Effects on Microstructure, Mechanical Properties, and Fracture Behaviour of 9Cr-1.5Mo-1Co-VNbBN Martensitic Steel Welded Joint for High Temperature Application

Abstract: This paper deals with long-term ageing effects of 9Cr-1.5Mo-1Co-VNbBN (CB2) steel weldment on its impact toughness, creep rupture behaviour, and hardness in relation to microstructure and fracture characteristics. The weldment was studied in PWHT state and after isothermal expositions at 625 ∘ C for 10000 and 30000 hours. Microstructure evolution was studied using analytical scanning and transmission electron microscopy. Charpy V-notch impact toughness tests were performed for all heat-treated states with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The knowledge about phase equilibria of the B-Cr-Fe system is important in several fields of materials research. The system is subsystem of various complex alloys, for example, modified ferritic steels for energy industry [1][2][3], steels for production abrasive, and corrosion-resistant components [4]. Information about the system is also important for study of boride coatings on various alloys and metals, including iron [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge about phase equilibria of the B-Cr-Fe system is important in several fields of materials research. The system is subsystem of various complex alloys, for example, modified ferritic steels for energy industry [1][2][3], steels for production abrasive, and corrosion-resistant components [4]. Information about the system is also important for study of boride coatings on various alloys and metals, including iron [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For welded joints of the steels P91 [3] and P92 [4], creep tests have shown that the fracture of the specimens under high load occurs in the weld metal (Type I) and is shifted into the heat affected zone (HAZ) at lower load and longer test duration (Type IV). Falat et al [5] describe a similar result for TIG welds in CB2 heat-resistant steel. However, such a shift of the fracture location from the weld metal into the HAZ does not always occur.…”
Section: Introductionmentioning
confidence: 56%
“…Few studies reported that the Z phase in the 9CrMoCoB matrix appears after aging for 67,857 h, and the formation of the Z phase consumes V, Nb, leading to a decrease in the strengthening of precipitate (Ref [22][23][24]. The 9CrMoCoB steel was subjected to a steam temperature of 650°C and a steam pressure of 50 to 120 MPa, and their longest service periods were 67,857 h and 82,649 h, respectively.…”
Section: Introductionmentioning
confidence: 99%